An Investigation of Age-Differentiated Conversations About Electronic Nicotine Delivery Systems on Reddit - Mario A. Navarro, PhD; Andrea Malterud, PhD; Zachary P. Cahn, PhD; Laura Baum, MA, MPH; Thomas Bukowski, MPA, MA; Caroline Kery, MS; Robert F. Chew, MS; Annice E. Kim, PhD (AJPM Focus, 2023)
Introduction: This study analyzes age-differentiated Reddit conversations about ENDS. Methods: This study combines 2 methods to (1) predict Reddit users’ age into 2 categories (13–20 years [underage] and 21–54 years [of legal age]) using a machine learning algorithm and (2) qualitatively code ENDS-related Reddit posts within the 2 groups. The 25 posts with the highest karma score (number of upvotes minus number of downvotes) for each keyword search (i.e., query) and each predicted age group were qualitatively coded. Results: Of 9, the top 3 topics that emerged were flavor restriction policies, Tobacco 21 policies, and use. Opposition to flavor restriction policies was a prominent subcategory for both groups but was more common in the 21–54 group. The 13–20 group was more likely to discuss opposition to minimum age laws as well as access to flavored ENDS products. The 21–54 group commonly mentioned general vaping use behavior. Conclusions: Users predicted to be in the underage group posted about different ENDS-related topics on Reddit than users predicted to be in the of-legal-age group.